Dancing in the rain and other essays - Jalil, Azizul, 1933- (Dhaka : University Press, 2009)
Chiefly autobiographical reminiscences of the author.
Keywords: Jalil, Azizul, -- 1933-; Jalil, Azizul, -- 1933- -- Travel; World Bank -- Officials and employees -- Biography; Pakistan -- Officials and employees -- Biography